Photocatalytic bleaching of aqueous malachite green solutions by UV-A and blue-light-illuminated TiO2 spherical nanoparticles modified with tungstophosphoric acid - Rengifo Herrera, Julian Andres (2011)
Visible-light-responsive spherical TiO2 particles were prepared by the sol–gel method by adding urea as pore-forming agent and tungstophosphoric acid (TPA) in different ratios (20% and 30% w/w) and by annealing at 500 ◦C for 2 h. Visible light absorption is probably due to WOx formation (i.e. WO3) resulting from the partial degradation of TPA and evidenced by XPS spectra. Besides, 31P NMR and XPS results showed evidence about the existence of mostly unaltered TPA within TiO2 nanoparticles and on their surface, together with lacunar or dimeric species. TPA addition not only affected the optical properties of materials but also produced a strong decrease of their point of zero charge (pHpzc). Results obtained under UV-A irradiation revealed that aqueous malachite green (MG) solutions were efficiently bleached through the oxidative process of N-demethylation being the TiO2 powder containing 30% (w/w) of TPA (TiO2–TPA–30%) (100% of bleaching in 60 min) the most active even than Degussa P-25 (80% of MG bleaching in 60 min). On the other hand, when blue-light irradiation was used, TiO2–TPA–30% powder also revealed the highest photocatalytic bleaching of MG solutions which, as in the case of UVA light irradiation experiments, was oxidized through N-demethylation processes. Finally, experiments carried out using blue-light irradiation under N2 atmosphere showed that aqueous MG solutions were not bleached by TiO2 powders containing TPA